Conhecimento e arte de educar : lições lockeanas - Rodrigues, Denilson Melo (2014)
Locke is one of the few philosophers who refer to education the decisive role of mold and interfere positively in the human development and consequently, in the formation of individual as a member of a society. To form citizenship is challenging act in view of the range of obstacles and difficulties that arise in this company. However it is undeniable that through the pedagogical act the human nature is modeled, that men become citizens, promoting in this way, the possibility of minimizing the individual desire in favor of welfare of a collectivity, since by reason the general interest overrides the private interest. The present study aims to analyze the relation ship between the mental processes that enable the knowledge and the education in the works An Essay on the Human Understanding and Some thoughts concerning education, other texts that make up the work of John Locke as bibliographic reference. The purpose to demonstrate that the construction of their pedagogical project is already present in a model of cognitive operation, whose methodological structure has its achievement condition in the experience, which, together connects to the moral and to the politics. Based on this structure of analysis, it becomes practicable to conceive the thought of the English philosopher that the methodology that guides the learning process of human knowledge is identical to that which allows the pedagogical formation of the man.